Paradigms under Pressure: Green Guidance - Peter Plant (Nordic Journal of Transitions, Careers and Guidance)
As the tectonic plates of society move, so do career guidance and career development. Old paradigms are under pressure. New guidance concepts are needed, some of which may be viewed as utopian. Guidance philosophies of our times need to envisage a shift towards a greener and sustainable future. Green Guidance puts a wider perspective to career choices and career development. Guidance needs a re-orientation, a new approach: a genuine paradigm shift. Resumé Samfundets tektoniske plader forskubber sig – og vejledning flytter med. Gamle paradigmer er under pres. Nye veje i vejledning er på vej. Måske ses de som utopiske. Men vejledning må bæres af en grøn og bæredygtig vision. Grøn vejledning bidrager med et bredere perspektiv på karriereudvikling. Vejledning behøver en ny-orientering: et paradimeskift.